Mechanical vibration isolation design for advanced clocking device and software design for environmental testing system - Neo, Ming Feng (2011)
With the development in the past decade, silicon Mircoelectromechanical Systems (MEMS) technology has reached a mature level. MEMS oscillators have been commercialized to emerge as a promising replacement for quartz crystals. They provide thinner and cheaper solution with easier integration for future electronics systems. As electronic systems miniaturize, oscillators are gradually exposed to environment with significant high frequency mechanical noise. This project focuses on the vibration isolation design for advanced clocking device in order to meet the mechanical vibration requirement. The design process is complemented by analytical solution and finite element analysis using ANSYS Workbench. Prototype of the design is fabricated with wire-cut electric discharge machining and experiments are conducted to match and verify the accuracy of both analytical and finite element analysis solutions. This project primarily studied on the effectiveness in vibration isolation of the design. MEMS oscillators‟ instability with temperature posed a challenge to the reliability of the timing device. This project also works on designing an Oscillator Environmental Testing System to acquire results of the performance of commercialized MEMS, crystal oscillators and oven-controlled crystal oscillators under temperature loadings. The result will be used as the performance benchmark for the design of advanced clocking device under temperature loading.